2011
DOI: 10.3138/jcfs.42.6.891
|View full text |Cite
|
Sign up to set email alerts
|

Family Adaptability, Cohesion and Anxiety During Pediatric Hospitalization: Differences between Populations of Immigrant and Non-immigrant Origin

Abstract: Different investigations have proved the existence of anxiety and emotional alteration in parents during the hospitalization of a child. The objective of this study was to investigate the potential association between some aspects of family functioning and emotional alterations. It’s centred concretely in parents’ anxiety during the hospitalization of a child, looking for differences between parents of immigrant and non-immigrant origin. Methods. One hundred and ninety one parents, aged 23 to 53, participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
1
0
5
Order By: Relevance
“…The needs of the immigrant population are somewhat different from those of the native population, and this entails constant work by hospital services (Fernández‐Castillo & Vílchez‐Lara, ). When comparing the emotional distress of immigrant and native populations, and specifically in parents of hospitalized children, some studies have found higher levels of stress, anxiety, fear, and mistrust in the immigrant population compared with the autochthonous (local) population (Fernández‐Castillo & Vílchez‐Lara, ; Fernández‐Castillo & Vílchez‐Lara, ; Fernández‐Castillo, Sada‐Lázaro, & Vílchez‐Lara, ; Fernández‐Castillo, Vílchez‐Lara, & Sada‐Lázaro, ). In contrast, some authors have found higher levels of satisfaction in the immigrant population compared with the native population (Fernández‐Castillo & Vílchez‐Lara, ).…”
mentioning
confidence: 99%
“…The needs of the immigrant population are somewhat different from those of the native population, and this entails constant work by hospital services (Fernández‐Castillo & Vílchez‐Lara, ). When comparing the emotional distress of immigrant and native populations, and specifically in parents of hospitalized children, some studies have found higher levels of stress, anxiety, fear, and mistrust in the immigrant population compared with the autochthonous (local) population (Fernández‐Castillo & Vílchez‐Lara, ; Fernández‐Castillo & Vílchez‐Lara, ; Fernández‐Castillo, Sada‐Lázaro, & Vílchez‐Lara, ; Fernández‐Castillo, Vílchez‐Lara, & Sada‐Lázaro, ). In contrast, some authors have found higher levels of satisfaction in the immigrant population compared with the native population (Fernández‐Castillo & Vílchez‐Lara, ).…”
mentioning
confidence: 99%
“…En relación con el funcionamiento familiar, nuestros resultados concuerdan con lo esperado a tenor de otros estudios en contextos sanitarios no de urgencias pediátricas 16 , donde niveles bajos de funcionamiento familiar se asociaban a nive-les elevados de otras alteraciones emocionales diferentes a las consideradas en este estudio. En aquella ocasión era la ansiedad la que mostraba niveles elevados cuando el funcionamiento familiar era deficitario.…”
Section: Discussionunclassified
“…Siendo estas alteraciones emocionales y específicamente la ira, variables asociadas a mayor insatisfacción en pacientes y familiares, tanto en servicios generales de urgencias como en servicios pediátricos 14,15 . En esta línea, estudios recientes han encontrado que la dificultad en el acceso a los servicios sanitarios, los tiempos de espera elevados, la información deficitaria o no comprendida, o la mayor gravedad percibida por los progenitores en sus hijos, son variables asociadas a mayores niveles de alteración emocional y en concreto a ira [16][17][18] .…”
Section: Introductionunclassified
See 2 more Smart Citations